Crime's Power
304 p.
Keywords: The changes that are engulfing the world today - the fall of nation-states and dictatorships, migrations and border crossings, revolution, democratization, and the international spread of capital - call for new approaches to the subject of crime. Anthropologists engage a variety of methods to answer that call in Crime's Power . Their view of crime extends into the intimacies of everyday life as war transforms personal identities, the violence of a serial killer inhabits paintings, and as the feel of imprisonment reveals society's potentials. Moving beyond the fixities of law, this book explores the nature of crime as an expression of power across the spectrum of human differences.